Efficacy of Botanical Insecticide Nanoemulsion Based on Tephrosia vogelii against Aphid Pests on Broccoli Plants - Putri Tama, Duma; Zahra, Varella; Nelly, Novri; Candra Lina, Eka (Jurnal Agrosci, 2024)
Aphids (Aphis gossypii) are a potential pest on broccoli plants (Brassica oleracea). The use of insecticides made from Tephrosia vogelii using nanoemulsion technology offers an environmentally friendly solution for this pest control. Nanoemulsion technology can produce very small particle sizes of nanometers that are adsorbed in liquids so that insecticides are more stable and effective. This study aims to test the effectiveness of botanical insecticide nanoemulsion made of Tephrosia vogelii against aphid pests on broccoli plants in the field. The research was carried out in the field, and the dose of field application refers to the results of laboratory research training (Tama, 2018). This study consisted of 4 treatments and six replicates, including K (Control), NTv (Nanoemulsion of vegetable insecticide made from T. vogelii), BT (bioinsecticide Bacillus thuringiensis), IS (synthetic insecticide with the active ingredient Abamectin). The results showed that the effectiveness of the three treatments included NTv 40.52%, BT 23.26%, IS 9.69%. There was a decrease in aphid populations in all three treatments. NTv (vegetable insecticide nanoemulsion made from T.vogelii) had the highest effect on aphids in broccoli plants in the field.